Ct guided reference markers for spinal dorsal lesions: A safe and valuable tool impacting intraoperative localization time. (February 2021) - Mongardi, Lorenzo; Visani, Jacopo; Mantovani, Giorgio; Olivetti, Maria Elena; Scerrati, Alba; Cultrera, Francesco; Ricciardi, Luca; De Bonis, Pasquale; Cavallo, Michele Alessandro; Lofrese, Giorgio
Highlights: Reduction of localization time with preoperative marker. Slightly improvement of effective dose (DAP). No related complication. Abstract: Background: Intraoperative localization of the correct spine level can be challenging when dealing with the thoracic spine; especially in morbidly obese patients and in mid-thoracic spine lesions. Different radiological reference markers techniques for dorsal surgery have been reported without a clear DAP (effective dose), localization and surgical time analysis. Purpose: The aim of the study is to analyze the radiological reference markers technique in terms of localization time and radiation dose during surgery for dorsal lesions. Methods: We used a radiopaque marker (fiducial) directly positioned before surgery over the lamina or the spinous process using CT scan for precise localization and vertebra count. We prospectively collected data about patients who underwent preoperative thoracic localization between April 2015 and September 2018 at Neurosurgery Department of Ferrara University Hospital. Clinical data as pathology, related surgical technique, radiological exams, localization time and radiation exposure were analyzed. Results: 19 patients who underwent preoperative radiopaque marker (fiducial) positioning and 11 patients who underwent fluoroscopy technique were enrolled. No complications related to fiducial placement and no wrong-level occurred. The localization time with the fiducial was reduced dramatically (3 min vs 15 min of the standard technique). The average DAP (effective dose) for the fiducial group was 20 Gy-cm 2 compared with 16 Gy-cm 2 of the traditional group. Conclusion: The use of preoperative fiducial for intraoperative localization of the target level in the thoracic spine dramatically reduce the location time without a significantly higher DAP (effective dose).